Analysis of the association between different domains and intensities of physical activity in adults: An observational and cross-sectional study - Christofaro, Diego G.D. [UNESP]; Tebar, William R. [UNESP]; Ferrari, Gerson; dos Santos, Amanda B. [UNESP]; Sasaki, Jeffer E.; Ritti-Dias, Raphael M.; Cucato, Gabriel G. (Public Library of Science (PLoS), 2024)
Background and objective To analyze the association between different domains and intensities of physical activity (PA) in adults. Methods 269 participants were randomly selected in a community-dwelling representative sampling process. The habitual PA practice was assessed in different domains (occupational, sports practice, and leisure time/commuting) using Baecke’s questionnaire and in different intensities (light, moderate, vigorous, and very vigorous) by accelerometry. Linear regression models analyzed the association between variables. Results Moderate and moderate-to-vigorous PA was positively associated with the three PA domain scores. Vigorous PA was associated with sports practice and leisure time/commuting PA. Only sports practice was associated with very vigorous-intensity PA (β = 1.32; 95% CI = 0.29; 2.35). Different associations were observed in stratified analyses according to sex and age groups. Men and younger participants showed an association of domain scores with higher intensity PA than their counterparts. Conclusion The findings suggest that higher intensities of PA were observed primarily in leisure time/ commuting PA and sports practice, and this association varied according to sex and age.